Faktor-faktor Perkawinan Usia Muda di Nagari Pakan Raba’a Tengah Kecamatan Koto Parik Gadang Diateh Kabupaten Solok Selatan - Yanti, Eriza; Suasti, Yurni (AHKAM, 2024)
This study aims to: 1) to find out the factors that most influence young marriage in Nagari Pakan Raba'a Tengah, Koto Parik Gadang Diateh District, South Solok Regency, and 2) to find out the social impact and economic impact of young marriage in Nagari Pakan Raba'a Tengah, Koto Parik Gadang Diateh District, South Solok Regency. This type of research uses qualitative methods. As for data collection by conducting observations, interviews, and documentation. The data source of this research uses primary data obtained and collected by researchers directly in the field and uses secondary data obtained from journals and related agencies. The results of this study reveal that the factors of young marriage are low education, family economy, already working, avoiding gossip slander, avoiding adultery, parental will, individual will, and getting pregnant outside of marriage in Nagari Pakan Raba'a Tengah, Koto Parik Gadang Diateh District, South Solok Regency and the social impact of young marriage in this Nagari in the form of a lack of interaction between couples who marry young and the surrounding community and the economic impact of young marriage in this Nagari in the form of difficulties in meeting the needs of life due to insufficient livelihoods.